STRATEGI PENGEMBANGAN PANTAI KEPO SEBAGAI DESTINASI WISATA PENYANGGA DI KABUPATEN SABU RAIJUA - Meliana Mamo Pe; Yudha Eka Nugraha; Lorens Riwu (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2022)
The purpose of this research is to formulate a development strategy for Kepo Beach as a buffer tourism destination in Sabu Raijua Regency. The method used in this research is a qualitative descriptive method by conducting observations, interviews, and direct documentation with several selected informants to support the success of this research. The results of this study indicate that there is a new development strategy that can be used to develop tourism at Kepo Beach to support leading tourism in Sabu Raijua Regency by applying the principles of supporting tourism development from the results of the SWOT analysis. It can be concluded that Kepo Beach has the potential and opportunities to develop in a better direction but it is necessary to use strengths to take advantage of opportunities, overcome weaknesses and threats by improving facilities and human resources at Kepo Beach.